Организационные факторы возведения одноэтажных промышленных зданий при использовании технологии совмещённого монтажа строительних конструкций и технологического оборудования - Лучинский, С. А. (Ways to Improve Construction Efficiency, 2014)
The article provides information on the process of combined installation of structures and technological equipment in the construction of industrial single-storey buildings. Methods of calculating the parallel streams, intensity and duration of work on the construction of industrial buildings, as well as the construction period buildings.